2022
DOI: 10.1021/acsami.2c15095
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Membrane Antigen Targeted Deep Tumor Penetration of Polymer Nanocarriers

Abstract: Tumoral uptake of large-size nanoparticles is mediated by the enhanced permeability and retention (EPR) effect, with variable accumulation and heterogenous tumor tissue penetration depending on the tumor phenotype. The performance of nanocarriers via specific targeting has the potential to improve imaging contrast and therapeutic efficacy in vivo with increased deep tissue penetration. To address this hypothesis, we designed and synthesized prostate cancer-targeting starPEG nanocarriers (40 kDa, 15 nm), [ 89 Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…Considering the threshold size for renal clearance ( Figure 3 A), Beckford-Vera and colleagues evaluated a series of non-targeted 4-armed starPEG nanocarriers of 40 kDa. The 89 Zr-labelled PET tracer demonstrated EPR-mediated high tumor uptake and retention in HT-29 and MX-1 tumor models [ 58 ], whereas they showed low uptake in PC3-Pip PCa xenograft [ 58 , 69 ]. Notably, various other macromolecules and NPs have shown low EPR-mediated tumor uptake in preclinical human PCa models such as PC3, DU-145, and CWR22rv1 [ 5 , 6 , 7 ].…”
Section: Psma-targeted Nanocarriersmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the threshold size for renal clearance ( Figure 3 A), Beckford-Vera and colleagues evaluated a series of non-targeted 4-armed starPEG nanocarriers of 40 kDa. The 89 Zr-labelled PET tracer demonstrated EPR-mediated high tumor uptake and retention in HT-29 and MX-1 tumor models [ 58 ], whereas they showed low uptake in PC3-Pip PCa xenograft [ 58 , 69 ]. Notably, various other macromolecules and NPs have shown low EPR-mediated tumor uptake in preclinical human PCa models such as PC3, DU-145, and CWR22rv1 [ 5 , 6 , 7 ].…”
Section: Psma-targeted Nanocarriersmentioning
confidence: 99%
“…Notably, various other macromolecules and NPs have shown low EPR-mediated tumor uptake in preclinical human PCa models such as PC3, DU-145, and CWR22rv1 [ 5 , 6 , 7 ]. Meher et al hypothesized and demonstrated that conjugation of ACUPA ligands to those starPEG nanocarriers can improve tumor uptake of EPR-low PCa models with enhanced tissue penetration and retention [ 69 ]. Three 4-arm StarPEG nanocarriers with or without distinctive numbers of PSMA-targeting ACUPA ligands were designed and synthesized ( Figure 14 A).…”
Section: Psma-targeted Nanocarriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, cancer has become the leading cause of death for people under 70, which reduces quality of life and life expectancy. , Chemotherapy is one of three main treatments for cancer that can effectively prolong the overall survival in patients with many types of metastatic cancer and even cure some metastatic cancers . However, most chemotherapy drugs such as docetaxel, paclitaxel, camptothecin, 5-fluorouracil, and cisplatin present shortcomings of poor water solubility, poor selectivity to tumor cells, low accumulation in tumor sites, and a short blood circulation half-life, which cause a series of adverse side effects and failure to achieve the ideal antitumor effect. In order to overcome the above drawbacks of chemotherapy drugs, a new drug delivery strategy is urgently needed. , In recent years, the rapid development of nanomedicine has provided a novel way for delivering chemotherapy agents. Since nanoparticles can penetrate into tumor tissue more easily and remain there through an enhanced permeability and retention (EPR) effect, numerous nano-drug delivery systems have been carefully designed for the purpose of delivering chemotherapy agents to the tumor site specifically. …”
Section: Introductionmentioning
confidence: 99%